Pengaruh Demihipo dan ZPT (Decamon®) terhadap Mortalitas Telur dan Serangan Lalat Pengorok Daun, Liriomyza huidobrensis (Blanchard) pada Tanaman Kentang - I Wayan Supartha (Jurnal Perlindungan Tanaman Indonesia, 2002)
Field experiment to determine the effectiveness of demihipo and Decamon® to induce the egg extrusion and reduce L. huidobrensis population larvae on potato was conducted in Pancasari, Buleleng (Bali) from February to August 1999. The results indicated that application of Decamon to the plant was significantly able to increase egg-extrusion of L. huidobrensis from the leaf compared with the other treatments. While, weekly application of insecticide (demihipo) was also significantly able to reduce the Larvae population on the plant. The application of the combination of both control measure (plant growth regulator or PGR) and insecticide (demihipo) was the most effective control to reduce the feeding or ovipositional-punctures of adult on the leaves. Therefore, the application of PGR and insecticide was the best to prevent and reduce the population development of L. huidobrensis in the field. In general, all control measures were able to increase the yield and advantage-added of the farmer. However, the highest increased of the yield and advantage-added in wet season were given by the plant treated with PGR (Decamon®), while in dry season given by the plant treated with the combination of PGR and demihipo.